SPE Eastern Regional Meeting 2002
DOI: 10.2118/78712-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cement: How Tough is Tough Enough? A Laboratory and Field Study

Abstract: Casing is cemented into the wellbore to provide zonal isolation of producing zones, protect fresh water zones from contamination, prevent casing collapse caused by moving salts or sloughing clays and isolate the casing from corrosive brines. In other words, casing is cemented to create annular isolation. Historically, the major physical property of the cement used to determine whether these results would be attained for the life of the well, was the unconfined compressive strength of the set cement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…One study suggests that a 100-psi compressive strength is sufficient to hold many casings in place (Mack and Dillenbeck 2002). Another study reported that a compressive strength of 500 psi is adequate for casing support (Stiles 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study suggests that a 100-psi compressive strength is sufficient to hold many casings in place (Mack and Dillenbeck 2002). Another study reported that a compressive strength of 500 psi is adequate for casing support (Stiles 1997).…”
Section: Resultsmentioning
confidence: 99%
“…One way is to prepare a mixture of coarse-and fine-cement particles, fly ash, fumed silica, hollow glass spheres, and water (Lea 1970). Another method is to add hollow glass or ceramic microspheres to plasticizer, cement, and a strengthening agent such as aluminum metal powder and sodium sulfate (Mack and Dillenbeck 2002).…”
Section: Introductionmentioning
confidence: 99%
“…One study indicates that a 100 psi compressive strength is enough for casings support (Mack, 2002). A compressive strength of 500 psi is enough for casing support according to another study (Stiles, 1997).…”
Section: Evaluation Of Hollow Glass Microspheres In Low Density Cemenmentioning
confidence: 99%
“…One study suggests that a 100 psi compressive strength is sufficient to hold many casings in place, Mack et al (2002). Another study reported that a compressive strength 500 psi is adequate for casing support, Stiles (1997).…”
Section: Compressive Strength Testmentioning
confidence: 99%